2017
DOI: 10.17696/2318-3691.24.3.2017.640
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização De Pacientes Reinternados No Setor De Cardiologia

Abstract: Conflito de interesses: NãoContribuição dos autores: ACMR tabulação dos dados, discussão dos achados, elaboração e redação do manuscrito, revisão crítica. NML concepção e planejamento do projeto de pesquisa, tabulação dos dados, discussão dos achados, orientação do projeto, redação e revisão crítica. AbstractIntroduction: Cardiovascular diseases are chronic diseases with high mortality rate. Thus, they represent a large demand for hospital services, contributing to a high number of hospital admissions and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…A study that related schooling levels to QLRH has shown that schooling levels are set as an important factor for the QL of heart diseases patients, and it is related to the prevalence of re-hospitalizations and mortality (12) . In agreement to a research carried out in Ribeirão Preto, São Paulo, Brazil (13) , the schooling levels of this study's sample was up to elementary school.…”
Section: Discussionmentioning
confidence: 99%
“…A study that related schooling levels to QLRH has shown that schooling levels are set as an important factor for the QL of heart diseases patients, and it is related to the prevalence of re-hospitalizations and mortality (12) . In agreement to a research carried out in Ribeirão Preto, São Paulo, Brazil (13) , the schooling levels of this study's sample was up to elementary school.…”
Section: Discussionmentioning
confidence: 99%
“…As informações sobre os medicamentos são fornecidas no momento da alta, e pacientes e famílias não são orientados sobre efeitos colaterais, recebendo apenas a receita médica, com dose, horário e via de administração (4), o que poderia gerar dúvidas após a alta e, por consequência, resultar em reinternações. Neste estudo, 12,4 % dos participantes foram readmitidos em até 30 dias após a alta, valor inferior ao identificado em estudo brasileiro realizado com pacientes cardíacos (27). Em investigações que utilizaram o CTM no âmbito internacional, encontram-se valores superiores (13) e valores inferiores de readmissão (1,22).…”
Section: Discussionunclassified
“…Sobre o motivo das readmissões, 30,8 % dos casos foram pelo mesmo motivo da internação anterior, e 61,5 % por doença inserida no mesmo grupo de classificação, o que está de acordo com investigações brasileiras realizadas com doentes crônicos e com comorbidades, as quais demonstraram porcentagens altas de readmissões pelo mesmo motivo (5,(27)(28). Estudo realizado em hospital público do estado de São Paulo, Brasil, identificou que as readmissões ocorreram pela mesma razão da internação anterior em 47,9 % dos pacientes (5).…”
Section: Discussionunclassified
“…2 The impact of HF is expected to increase substantially, as a result of increased survival of CAD patients, in combination with population ageing. 6,7 This raises the need for registers to project, conduct and better understand this population of heterogeneous patients.…”
Section: Introductionmentioning
confidence: 99%